Nutrient uptake, harvest and addition by crops under different cropping sequences (Dhaka University Journal of Biological Sciences, 2011)
A field trial was conducted to determine the nutrient uptake, harvest and addition by different crops under jute included and jute excluded cropping sequences. The crops were potato (Solanum tuberosum L.), jute (Corchorus olitorius L.), broadcast aus rice and transplanted aman rice (Oryza sativa L.). The soil of the experimental site represents Melandha soil series under noncalcareous brown floodplain soil (General Soil Type) which belongs to Agro Ecological Zone No. 8 (Young Brahmaputra and Jumuna Floodplain). Experiment was conducted with potato as base crop in rabi season for three consecutive years in the same field. The treatments (cropping patterns) were Potato - Jute - T. aman, Potato - B. aus - T. aman, Potato - Fallow - T. aman, and Fallow - Jute - T. aman. Jute plant harvested the lowest amount of nutrients and added back the highest amount to the soil. Contributions to the additions of nutrients by crops followed the following sequence: for nitrogen jute > B. aus > T. aman > potato; for phosphorus jute > T. aman > B. aus > potato; for potassium jute > B. aus > T.aman > potato, and for sulphur jute > B. aus > T. aman > potato.Key words: Nutrient uptake; Harvest; Addition; Cropping sequenceDOI: http://dx.doi.org/10.3329/dujbs.v20i1.8874Dhaka Univ. J. Biol. Sci. 20(1): 81-89, 2011 (January)